Failure analysis method of concrete arch dam based on elastic strain energy criterion. (February 2016) - Chen, Bo; Gu, Chongshi; Bao, Tengfei; Wu, Bangbin; Su, Huaizhi
Abstract: The arch dam is a type of massive water-retaining structure made of concrete. The overall failure mechanism and corresponding analysis criterion are key issues of concern in the dam engineering field. In this paper, the energy evolution of arch dams in the failure process is studied first, which can be decomposed as energy dissipation accompanied by concrete damage and elastic strain energy absorption and release during elastic deformation. An evaluation criterion for failure analysis of concrete arch dams is then established based on elastic strain energy. An orthotropic damage constitutive model for dam concrete is then proposed along with its numerical simulation method, which is established for structural failure analysis. Numerical simulations show that the elastic strain energy in elements increases with increasing overload safety coefficient and finally converges to the concrete material surface energy, at which time the locally plastic damage area develops rapidly and finally leads to cracking failure of structures. The proposed failure analysis criterion for concrete dams under integrated loads is suitable for analyzing dam instability failure, which has great operability and value in engineering applications in the future. Highlights: We establish a failure evaluation criterion based on elastic strain energy. An orthotropic damage constitutive model is developed for numerical simulation. The growth elastic strain energy will converge to material surface energy. Local plastic damage and crack failure develop rapidly if the criterion is satisfied.